Slope Stability Analysis Using Spencer Method in Pit 1 Area of Limestone Mining PT Sumbar Calsium Pratama, Nagari Halaban, Lareh Sago Halaban, Lima Puluh Kota, West Sumatera - Muhammad Irfan (Departemen Teknik Pertambangan FT UNP, 2024)
PT Sumbar Calcium Pratama as one of the mining companies that produces calcium material for core and shell separators for the palm oil mill industry, participates by increasing production to meet consumer needs. PT Sumbar Calcium Pratama is one of the mining companies engaged in the mining of class C excavation material (limestone) whose mining operations are carried out by means of Quarry. The results of taking slope geometry data at PT Sumbar Calsium Pratama obtained a slope height of 30 m with a slope angle of 83 °. The Spencer Slice Method was developed by Spencer in 1967. It is one of the most theoretically rigorous wedge methods because it fulfills the balance of forces and moments of the collapsing mass. Thus, it allows for a more precise calculation of the Factor of Safety (FS). The results of the Rock Mass Rating (RMR) analysis of the rock show that the Rock Quality Designation (RQD) of the rock mass of the slope in the pit 1 mining area of PT Sumbar Calsium Pratama has a slope of 2.58%, and the weight of the Rock Mass Rating (RMR) of the slope belongs to class III (medium). Kinematic analysis then obtained the potential for landslides that will occur in the research area in the form of plane avalanches (Planar Failure) of 10%, wedge avalanches (Wedge Failure) of 9.47%, avalanches (Flexural toppling) of 45%. Recommendations in an effort to increase the stability of the research slope of PT Sumbar Calsium Pratama which is in a saturated state is not stable / safe, first by changing the slope geometry in the form of slope height which was originally 30 meters to 24 m or 23 m then obtained FK values of 1.33 and 1.37 (safe / stable). Second, by reducing the slope from 83° to 65° and 64°, FK values of 1.3 and 1.38 (safe/stable) were obtained.